Documentation in Medical Practice (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Many Doctors do not follow proper documentation of medical Records. In fact many  of them do not realize the importance of documenting their records thoroughly,  thereby exposing them to frivolous charges of malpractice. This paper seeks to  impress upon the importance of proper medical documentation and its medico legal  significance. The materials are collected by reviewing medical records of KMC  hospitals and Govt. Wenlock hospital, Mangalore, India along with medical registers  of medical record departments of above-mentioned hospitals. For additional  information the listed references were consulted.
Keywords: Medical Records; Documentation; Documentary Evidence